Microfluidic Multitissue Platform for Advanced Embryotoxicity Testing In Vitro. Issue 13 (29th April 2019) - Boos, Julia Alicia; Misun, Patrick Mark; Michlmayr, Astrid; Hierlemann, Andreas; Frey, Olivier
Abstract: The integration of metabolic competence in developmental toxicity assays in vitro is of fundamental importance to better predict adverse drug effects. Here, a microfluidic hanging‐drop platform is presented that seamlessly integrates liver metabolism into the embryonic stem cell test (EST). Primary human liver microtissues (hLiMTs) and embryoid bodies (EBs) are combined in the same fluidic network, so that hLiMT‐generated metabolites are directly transported to the EBs. Gravity‐driven flow through the network enables continuous intertissue communication, constant medium turnover, and, most importantly, immediate exchange of metabolites. As a proof of concept, the prodrug cyclophosphamide is investigated and a fourfold lower ID50 concentration (50% inhibition of EB differentiation) is found after biotransformation, which demonstrates the potentially adverse effects of metabolites on embryotoxicity. The metaEST platform provides a promising tool to increase the predictive power of the current EST assay by more comprehensively including and better reflecting physiological processes in in vitro tests. Abstract : A microfluidic hanging‐drop platform is presented, which seamlessly integrates liver metabolism into the embryonic stem cell test (EST). Primary human liver microtissues and embryoid bodies are cocultured in a single, gravity‐driven fluidic network, which enables the investigation of the effect of prodrugs on early embryonic development to increase the predictive power of in vitro developmental toxicity assays.